Surface Roughness Analysis and Optimization of CNC Lathe Machining Parameters in the Manufacturing of Motorcycle Brake Master Cylinder Piston - Novaldi Andryoga; Anita Susilawati (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2022)
This study aims to optimize the machining parameters in the manufacture of Yamaha motorcycle brake piston master cylinder and determine the effect on surface roughness. The method used is the Taguchi method. Machining parameters were varied based on the Taguchi method, each of which was experimented with using a finishing CNC lathe machine. From these experiments, the results obtained in the form of surface roughness values ​​which were then analyzed, in order to obtain the best parameters with the smallest surface roughness values ​​and the effect of each factor on surface roughness. This research produces the best parameters are spindle speed 1.755 RPM, feed rate 0.09 mm/rev, and depth of cut 0.30 mm. This parameter has a small surface roughness value. Based on surface roughness measurements, the factors that have the greatest influence on the level of surface roughness are feedrate of 67.9%, spindle speed of 15.4% and depth of cut of 3.3%. This proves that the smaller the value of feedrate, spindle speed and depth of cut, the smaller the value of surface roughness will be.